Le développement des agricultures durables dans la région andine de Cusco : quelle proximité socio-économique entre conseillers agricoles, producteurs et consommateurs ? - Margaux Girard (Développement Durable et Territoires)
Since 2000, different models of sustainable agriculture and short food chains emerged in the Cusco region, in the Peruvian Andes. These models theoretically imply a reterritorialization of the agro-food system characterized, among other things, by a search for new proximities between the actors of the system, in particular between agricultural advisors, producers and consumers: a spatial proximity but also a socio-economic proximity. We note that this dynamic of territorial agri-food system greening generates contrasting socio-economic proximity relations between these actors, dominated by significant differences in living standards and lifestyles but where minority strategies of rapprochement are put in place.